2017
DOI: 10.1159/000476068
|View full text |Cite
|
Sign up to set email alerts
|

ZNF750 Expression as a Novel Candidate Biomarker of Chemoradiosensitivity in Esophageal Squamous Cell Carcinoma

Abstract: Objective: ZNF750, an epidermal differentiation regulator, has been suggested to act as a tumor suppressor of esophageal squamous cell carcinoma (ESCC). Although a correlation between the epidermal differentiation gene and resistance to chemoradiotherapy (CRT) has been posited, no data regarding the ZNF750 status in ESCC have been reported. The aim of the present study was to evaluate the relationship between ZNF750 expression and response to CRT in ESCC. Methods: Eighty-seven patients who had been pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Zinc Finger Protein 750 (ZNF750), as a transcription factor belonging to one of the Zinc Finger Protein family members, was the top-ranked hypomethylated gene in the dataset. Previous findings revealed that ZNF750 serves as a tumor repressor in oral squamous cell carcinoma 6 and esophageal squamous cell carcinoma 7 . However, the mechanism by ZNF750 governs tumorigenesis and the role of ZNF750 in NPC remain largely unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Zinc Finger Protein 750 (ZNF750), as a transcription factor belonging to one of the Zinc Finger Protein family members, was the top-ranked hypomethylated gene in the dataset. Previous findings revealed that ZNF750 serves as a tumor repressor in oral squamous cell carcinoma 6 and esophageal squamous cell carcinoma 7 . However, the mechanism by ZNF750 governs tumorigenesis and the role of ZNF750 in NPC remain largely unknown.…”
Section: Introductionmentioning
confidence: 97%
“…In other words, ZNF750 is associated with KLF4, a tumor suppressor gene, and is considered to have an important role in treatment resistance. Indeed, we previously revealed that a low ZNF750 expression was associated with poor sensitivity to chemoradiotherapy [11]. In addition, Hu et al [30] revealed that the upregulation of KLF4 by methylseleninic acid could inhibit cell growth in ESCC cells.…”
Section: Discussionmentioning
confidence: 94%
“…ZNF750 was reported to act as a transcriptional regulator of epidermal differentiation, and the expression of ZNF750 induces epidermal differentiation genes and suppresses epidermal progenitor genes [9]. ZNF750 has been shown to function as a tumor suppressor [5,6,10], and we previously reported the relationship between ZNF750 expression and chemoradiotherapy response in ESCC patients [11]. We, therefore, consider ZNF750 to be a notable gene in the field of ESCC.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, high levels of ZNF750 are associated with a good response to chemoradiotherapy, suggesting that ZNF750 could serve as a novel candidate biomarker for chemoradiotherapy sensitivity. 75 …”
Section: Role Of Znfs In Diseasesmentioning
confidence: 99%